(untitled) (Bangladesh Journal of Livestock Research, 2020)
Producing and trading of green fodder are recognised as a profitable venture in many parts of the country, but data and information in this aspect are very scanty. The study determined the income coefficient of fodder farm households to study the fodder marketing and processing in different locations, and highlighted farmers problems related to fodder marketing and processing. In this regard, four study areas were selected from four districts viz: Dinajpur, Jessore, Kurigram and Rangpur purposively considering the concentration of fodder production and marketing. A purposive sampling technique was followed for collecting primary data from the field. In the study 3 categories of sample farmers were selected namely: i) Fodder Producer cum seller; ii) Fodder Producer cum Dairy owner having 1-2 dairy cows as small, 3-4 dairy cows as medium and 5 and above dairy cows as large farmer and iii) Fodder Middlemen. A total of 200 fodder farmers were interviewed. Field survey method and focus group discussions were followed to collect necessary data and information. Descriptive statistics and Cobb Douglas type revenue function were applied to meet the objectives and to get the desirable outputs. Functional analysis revealed that fodder sale and livestock rearing and fodder business significantly contributed to the household income of the fodder farmers and middlemen. The dairy farmers having 1-2, 3-4 and 4-5 cross-bred dairy cattle earned Tk. 1,20,227, Tk. 1,91,728 and Tk. 4,17,287, respectively, whereas local cattle earned Tk. 33, 658, Tk. 51,601 and Tk. 1,13,558, respectively from milk sell annually. It was found that fodder middlemen’s income from fodder business highest in Kurigram district and lowest in Jessore district. Fodder processing was not happened in the study areas. Main marketing channels were: (i) Producer cum seller-Dairy owner and (ii) Producer cum seller-Fodder Middlemen-Dairy owner. Fodder farmers faced various socioeconomic problems during its processing and marketing. The major problems were the lack of HYV fodder species, lack of knowledge, lack of input facilities, and lack of marketing facilities. The government should provide HYV fodder, cultivation training, preservation technique, and organized market to the fodder farmers in the study areas. Bangladesh J. of Livestock Res. 21-25: 133-141, 2018